'Girly Latina versus girly American': the articulation of levels of femininity through indexicality in a Latina student's narrative explaining discriminatory classroom interactions. (29th December 2016) - Rojas-Sosa, Deyanira
Abstract : The construction of gender and race are constantly negotiated by community members, and both categories affect the way speakers see themselves and others. By analysing a Latina student's narrative, this study explores how she articulates through the use of several indexical processes, not only her own identity but also her friend's, in order to explain how their classmates perceive them. In this narrative, the speaker explains how different levels of femininity, 'girly American' versus 'girly Latina', affect the way Latinas are perceived and, in some cases, treated in discriminatory ways. This analysis finds that her articulation of different levels of femininity, and her arguments about how different stereotypes associated with Latinas may cause discrimination, shows how the construction of gender and race are interrelated and fluid, and how there are certain performances of gender more acceptable than others even within the heterosexual norm. This analysis shows how language practices are fundamental to create and circulate ideologies about gender and ethnicity, and how essential it is to understand these practices in order to recognise and challenge the discrimination faced by minority groups in the United States, especially women of colour.